Nest camouflage records on five social wasp species (Vespidae, Polistinae) from southeastern Brazil - Souza , Marcos Magalhães de; Clemente, Mateus Aparecido; Teofilo-Guedes, Gabriel (EntomoBrasilis, 2020)
Social insects use different strategies to defend their colonies, including camouflage. In order to expand knowledge, regarding the strategy of camouflage in social wasps, information is presented on the camouflage pattern of the species: Parachartergus smithii (De Saussure), Parachartergus wagneri Du Buysson, Chartergellus communis Richards, Metapolybia cingulata (Fabricius) and Mischocyttarus anthracinus Richards.These species are uncommon in inventory studies in Brazil. Records occur in different Conservation Units, between 2011 and 2019, in the Minas Gerais State, Brazil Southeastern. Camouflage seems to be the main defense strategy for these species, due to the color and shape of their nests in line with the substrate, as well as their docile behavior. The exception is Metapolybia cingulata, which in addition to camouflage shows aggressive behavior in some situations, which suggests the use of different strategies in the colony defense.